2020
DOI: 10.1101/2020.08.17.255166
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seeding of outbreaks of COVID-19 by contaminated fresh and frozen food

Abstract: An explanation is required for the re-emergence of COVID-19 outbreaks in regions with apparent local eradication. Recent outbreaks have emerged in Vietnam, New Zealand and parts of China where there had been no cases for some months. Importation of contaminated food and food packaging is a feasible source for such outbreaks and a source of clusters within existing outbreaks. Such events can be prevented if the risk is better appreciated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 2 publications
4
76
0
Order By: Relevance
“…In this regard, Fisher et al (51) found that infectious SARS-CoV-2 did not decline in titer and was able to survive for 3 weeks in inoculated pieces of chicken, pork and salmon stored at 4, −20, and −80 • C. Furthermore, Mullis et al (52) demonstrated that a bovine coronavirus present on lettuce stored at 4 • C retained its infectivity for at least 14 days. In addition, coronavirus 229E survived well for 2 days on lettuce stored at 4 • C, before quickly decreasing in numbers, but did not survive on the surface of strawberries, potentially because of the acidity (53).…”
Section: Survival and Inactivation Of Sars-cov-2 In Foodmentioning
confidence: 99%
“…In this regard, Fisher et al (51) found that infectious SARS-CoV-2 did not decline in titer and was able to survive for 3 weeks in inoculated pieces of chicken, pork and salmon stored at 4, −20, and −80 • C. Furthermore, Mullis et al (52) demonstrated that a bovine coronavirus present on lettuce stored at 4 • C retained its infectivity for at least 14 days. In addition, coronavirus 229E survived well for 2 days on lettuce stored at 4 • C, before quickly decreasing in numbers, but did not survive on the surface of strawberries, potentially because of the acidity (53).…”
Section: Survival and Inactivation Of Sars-cov-2 In Foodmentioning
confidence: 99%
“…Most of the evidence on SARS-CoV-2 detection on frozen foods appeared between July-August 2020, weeks or months later after the recent discussions on food-associated transmission of COVID-19 (Ceylan et al 2020;Eslami and Jalili 2020;Rizou et al 2020;Sharma et al 2020;Zuber and Brüssow 2020). Further, studies on the stability of SARS-CoV-2 in food environments only began to appear in early July 2020 (Fisher et al 2020;Harbourt et al 2020). These critical developments called for an updated and more informed view on this matter, by reviewing new evidence, scholarly discussions, and current policy and knowledge gaps.…”
Section: Environmental Chemistry Lettersmentioning
confidence: 99%
“…With respect to food environments, there has been only one study to date on the survival of SARS-CoV-2 on food surfaces. In a controlled laboratory study, Fisher et al (2020) examined the persistence of SARS-CoV-2 on refrigerated and frozen salmon, chicken, and pork over a period of 21 days. The study found that the titers of SARS-CoV-2 remained virtually constant, and the inoculated viruses maintained their infectivity on both refrigerated (4 °C) and frozen (− 20 °C and − 80 °C) samples.…”
Section: Food Contamination and The Cold Chainmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, demand for fresh/frozen seafood for high-value auction and retail outlets dropped, which impacted the longliners that supply these markets. The reopening of Chinese markets in the Spring of 2020 for fresh/frozen seafood may have eased some of these bottlenecks, although recent evidence that the COVID-19 virus can survive on frozen foods for several weeks, and may even have been responsible for several outbreaks in Asia, might lead to new slowdowns in seafood trade and retailing (Fisher et al 2020).…”
Section: A Destabilized Seafood Systemmentioning
confidence: 99%